(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Together with a broad range of other enabling technologies, blockchain generates the genuinevalue for the populace and the economy. In order to effectively employ artificial intelligence in thehealthcare sector, there are a number of challenges that must be solved, including privacy issues, a lackof large-scale, high-quality data sets, the requirement for high dimensionality, high sensitivity, and highspecificity. By employing blockchain as the method, the current inefficiency problem in the financialsector may be alleviated. The potential of blockchain technology is already being explored by more than45 financial institutions. The research showed that this technology is still in its early stages ofdevelopment. The more thorough analysis, suggestions, and real-world examples. The study addressesboth the applicability of blockchain technology and the many initiatives that have been discussed in theUAE and throughout the globe. In the background, there was some conversation concerning thedevelopment of BC technology. The most crucial step was to do study to determine how well BCtechnology will work in the UAE.